A case of high obesity robot assisted radical resection of low rectal cancer - Xiao-Chun ZHANG; Guan-Wen GONG; Jun-Jie GUAN; Zheng-Ming DENG; Jiang LIU; Zhi-Wei JIANG (Yixue xinzhi zazhi, 2023)
Rectal cancer combined with high obesity has become a major social problem, which has high surgical difficulty, high intraoperative risk and high incidence of postoperative complications. Since the rise of Da Vinci robot, it has been widely used, and its application in gastrointestinal tumors is increasingly mature. It has distinct advantages in the application of low rectal cancer patients with high obesity. A 59 year old female patient was admitted to the Affiliated Hospital of Nanjing University of Chinese Medicine. Preoperative diagnosis of rectal malignant tumor, BMI was 34.60 kg/m2. After multidisciplinary evaluation before operation, robot assisted laparoscopic total mesorectal excision was performed. The operation was smooth and the effect was satisfactory.